Indicators for gender equality and the empowerment of women: from concept to practice - Chavarro, Mónica Juliana; Moreno, Manuel; Muriel, Juliana; Twyman, Jennifer (2020)
Nowadays, there is a great interest in incorporating gender into agricultural development projects. However, its incorporation does not ensure the reduction of inequalities, because the theoretical concepts of gender, empowerment, and equality are not always defined or articulated with their implementation in practice. The lack of articulation between the concept of gender and its application in different projects results in a formulation and implementation that are weak in terms of operationalization, making it difficult to: capture the full range of dimensions considered by empowerment and gender equality; design and implement actions in favor of women; reduce the inequalities between men and women; and contribute to the achievement of Sustainable Development Goal number 5 “Gender Equality”. The lack of guidelines on how to connect the concepts of gender equality and/or women’s empowerment with practice unveils the need to know what indicators to use or adapt (and how to adapt them) to measure the concepts related to gender. This is why, through a systematic review of literature, in this study, we seek to show evidence of the ways in which the concepts of gender have been operationalized by agricultural development projects in Latin America, with the purpose of approaching the discussion on the need of methodological guidelines to apply gender analysis.